(untitled) (Ameghiniana, 2013)
Two new species, of Gleichenites and Elatocladus respectively, are described. Additionally, a few forms previously not mentioned for this flora are also described. No change of the Middle ]urassic age, already established by Bonetti (1), resulted from the analysis of the elements here added.